Excessive Daytime Sleepiness pada siswa MTsN 02 Makassar: Studi Komparasi Perbedaan Durasi Tidur - Fadli, Muhammad Nur; Ismalandari Ismail; Rahmat Permadi (CV. ULIL ALBAB CORP, 2026)
Excessive daytime sleepiness has a significant impact on students’ health and quality of life. This study aims to examine excessive daytime sleepiness in relation to nighttime sleep duration on school days and non-school days among students of MTSN 02 Makassar. The respondents in this study were 40 students aged 12–15 years, selected using the accidental sampling technique. The research utilized the Cleveland Adolescent Sleepiness Questionnaire (CASQ) and was analyzed using the Mann–Whitney test. The results showed that there was no significant difference in excessive daytime sleepiness based on nighttime sleep duration between school days and non-school days among the students of MTSN 02 Makassar.